Personality profiles of effective leadership performance in assessment centers. Issue 2 (14th March 2016) - Parr, Alissa Denzin; Lanza, Stephanie T.; Bernthal, Paul
ABSTRACT: Most research examining the relationship between effective leadership and personality has focused on individual personality traits. However, profiles of personality traits more fully describe individuals, and these profiles may be important as they relate to leadership. This study used latent class analysis to examine how personality traits combine and interact to form subpopulations of leaders and how these subpopulations relate to performance criteria. Using a sample of 2, 461 executive-level leaders, six personality profiles were identified: Unpredictable Leaders with Low Diligence (7.3%); Conscientious, Backend Leaders (3.6%); Unpredictable Leaders (8.6%); Creative Communicators (20.8%); Power Players (32.4%); and Protocol Followers (27.1%). One profile performed well on all criteria in an assessment center; remaining profiles exhibited strengths and weaknesses across criteria. Implications and future directions for research are highlighted.